Assessing genetically modified cotton’s economic impact on farmers - Horna, Daniela; Falck-Zepeda, José B.; Kyotalimye, Miriam (International Food Policy Research Institute, 2013)
In Uganda, cotton has been characterized as a crop with relatively low profitability, mostly due to low productivity (Baffes 2009), but also because it is affected by fluctuations in cotton’s world price. Studies done by APSEC (1998, 2001) ranked cotton as the lowest in profitability among the main competing crops on the global market. Despite cotton’s low profitability, farmers continue to plant it. The most-often-cited reason for continued cotton production is a lack of productive alternatives that can generate cash for smallholders and larger farmers during the period cotton is planted. The certainty that cotton producers will have a buyer at the end of the season is probably another strong argument for cotton cultivation: ginneries usually distribute seed and inputs and in turn demand rights over the seed cotton harvest at the end of the cropping season.